Termination w.r.t. Q of the following Term Rewriting System could be proven:
Q restricted rewrite system:
The TRS R consists of the following rules:
b(b(b(x1))) → a(b(x1))
a(a(x1)) → a(b(a(x1)))
a(a(a(x1))) → a(b(b(x1)))
Q is empty.
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
Q restricted rewrite system:
The TRS R consists of the following rules:
b(b(b(x1))) → a(b(x1))
a(a(x1)) → a(b(a(x1)))
a(a(a(x1))) → a(b(b(x1)))
Q is empty.
Using Dependency Pairs [1,15] we result in the following initial DP problem:
Q DP problem:
The TRS P consists of the following rules:
A(a(a(x1))) → B(x1)
A(a(x1)) → A(b(a(x1)))
B(b(b(x1))) → A(b(x1))
A(a(a(x1))) → B(b(x1))
A(a(a(x1))) → A(b(b(x1)))
A(a(x1)) → B(a(x1))
The TRS R consists of the following rules:
b(b(b(x1))) → a(b(x1))
a(a(x1)) → a(b(a(x1)))
a(a(a(x1))) → a(b(b(x1)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
A(a(a(x1))) → B(x1)
A(a(x1)) → A(b(a(x1)))
B(b(b(x1))) → A(b(x1))
A(a(a(x1))) → B(b(x1))
A(a(a(x1))) → A(b(b(x1)))
A(a(x1)) → B(a(x1))
The TRS R consists of the following rules:
b(b(b(x1))) → a(b(x1))
a(a(x1)) → a(b(a(x1)))
a(a(a(x1))) → a(b(b(x1)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
The approximation of the Dependency Graph [15,17,22] contains 1 SCC with 1 less node.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
A(a(a(x1))) → B(x1)
A(a(x1)) → A(b(a(x1)))
B(b(b(x1))) → A(b(x1))
A(a(a(x1))) → B(b(x1))
A(a(a(x1))) → A(b(b(x1)))
The TRS R consists of the following rules:
b(b(b(x1))) → a(b(x1))
a(a(x1)) → a(b(a(x1)))
a(a(a(x1))) → a(b(b(x1)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By narrowing [15] the rule A(a(x1)) → A(b(a(x1))) at position [0] we obtained the following new rules:
A(a(a(a(x0)))) → A(b(a(b(b(x0)))))
A(a(a(x0))) → A(b(a(b(a(x0)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
A(a(a(x1))) → B(x1)
A(a(a(x0))) → A(b(a(b(a(x0)))))
B(b(b(x1))) → A(b(x1))
A(a(a(x1))) → B(b(x1))
A(a(a(x1))) → A(b(b(x1)))
A(a(a(a(x0)))) → A(b(a(b(b(x0)))))
The TRS R consists of the following rules:
b(b(b(x1))) → a(b(x1))
a(a(x1)) → a(b(a(x1)))
a(a(a(x1))) → a(b(b(x1)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By narrowing [15] the rule A(a(a(x1))) → A(b(b(x1))) at position [0] we obtained the following new rules:
A(a(a(b(x0)))) → A(a(b(x0)))
A(a(a(b(b(x0))))) → A(b(a(b(x0))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
A(a(a(x1))) → B(x1)
A(a(a(b(b(x0))))) → A(b(a(b(x0))))
A(a(a(x0))) → A(b(a(b(a(x0)))))
A(a(a(b(x0)))) → A(a(b(x0)))
B(b(b(x1))) → A(b(x1))
A(a(a(x1))) → B(b(x1))
A(a(a(a(x0)))) → A(b(a(b(b(x0)))))
The TRS R consists of the following rules:
b(b(b(x1))) → a(b(x1))
a(a(x1)) → a(b(a(x1)))
a(a(a(x1))) → a(b(b(x1)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By narrowing [15] the rule B(b(b(x1))) → A(b(x1)) at position [0] we obtained the following new rules:
B(b(b(b(b(x0))))) → A(a(b(x0)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ ForwardInstantiation
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
A(a(a(x1))) → B(x1)
A(a(a(b(b(x0))))) → A(b(a(b(x0))))
A(a(a(x0))) → A(b(a(b(a(x0)))))
A(a(a(b(x0)))) → A(a(b(x0)))
A(a(a(x1))) → B(b(x1))
B(b(b(b(b(x0))))) → A(a(b(x0)))
A(a(a(a(x0)))) → A(b(a(b(b(x0)))))
The TRS R consists of the following rules:
b(b(b(x1))) → a(b(x1))
a(a(x1)) → a(b(a(x1)))
a(a(a(x1))) → a(b(b(x1)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By forward instantiating [14] the rule A(a(a(x1))) → B(b(x1)) we obtained the following new rules:
A(a(a(b(b(b(y_0)))))) → B(b(b(b(b(y_0)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ ForwardInstantiation
↳ QDP
↳ ForwardInstantiation
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
A(a(a(x1))) → B(x1)
A(a(a(b(b(x0))))) → A(b(a(b(x0))))
A(a(a(b(b(b(y_0)))))) → B(b(b(b(b(y_0)))))
A(a(a(x0))) → A(b(a(b(a(x0)))))
A(a(a(b(x0)))) → A(a(b(x0)))
B(b(b(b(b(x0))))) → A(a(b(x0)))
A(a(a(a(x0)))) → A(b(a(b(b(x0)))))
The TRS R consists of the following rules:
b(b(b(x1))) → a(b(x1))
a(a(x1)) → a(b(a(x1)))
a(a(a(x1))) → a(b(b(x1)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By forward instantiating [14] the rule A(a(a(x1))) → B(x1) we obtained the following new rules:
A(a(a(b(b(b(b(y_0))))))) → B(b(b(b(b(y_0)))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ ForwardInstantiation
↳ QDP
↳ ForwardInstantiation
↳ QDP
↳ SemLabProof
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
A(a(a(b(b(b(b(y_0))))))) → B(b(b(b(b(y_0)))))
A(a(a(b(b(x0))))) → A(b(a(b(x0))))
A(a(a(b(b(b(y_0)))))) → B(b(b(b(b(y_0)))))
A(a(a(x0))) → A(b(a(b(a(x0)))))
A(a(a(b(x0)))) → A(a(b(x0)))
B(b(b(b(b(x0))))) → A(a(b(x0)))
A(a(a(a(x0)))) → A(b(a(b(b(x0)))))
The TRS R consists of the following rules:
b(b(b(x1))) → a(b(x1))
a(a(x1)) → a(b(a(x1)))
a(a(a(x1))) → a(b(b(x1)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
We found the following quasi-model for the rules of the TRS R.
Interpretation over the domain with elements from 0 to 1.B: 0
a: 0
A: 0
b: 1
By semantic labelling [33] we obtain the following labelled TRS:Q DP problem:
The TRS P consists of the following rules:
A.0(a.0(a.1(b.1(b.0(x0))))) → A.0(b.0(a.1(b.0(x0))))
B.1(b.1(b.1(b.1(b.1(x0))))) → A.0(a.1(b.1(x0)))
A.0(a.0(a.1(b.1(b.1(b.1(b.0(y_0))))))) → B.1(b.1(b.1(b.1(b.0(y_0)))))
A.0(a.0(a.1(b.1(b.1(b.0(y_0)))))) → B.1(b.1(b.1(b.1(b.0(y_0)))))
A.0(a.0(a.0(x0))) → A.1(b.0(a.1(b.0(a.0(x0)))))
A.0(a.0(a.0(a.1(x0)))) → A.0(b.0(a.1(b.1(b.1(x0)))))
A.0(a.0(a.1(x0))) → A.0(b.0(a.1(b.0(a.1(x0)))))
A.0(a.0(a.1(b.1(b.1(x0))))) → A.1(b.0(a.1(b.1(x0))))
A.0(a.0(a.0(x0))) → A.0(b.0(a.1(b.0(a.0(x0)))))
A.0(a.0(a.1(b.1(b.0(x0))))) → A.1(b.0(a.1(b.0(x0))))
A.0(a.0(a.1(b.1(b.1(x0))))) → A.0(b.0(a.1(b.1(x0))))
A.0(a.0(a.1(x0))) → A.1(b.0(a.1(b.0(a.1(x0)))))
A.0(a.0(a.0(a.1(x0)))) → A.1(b.0(a.1(b.1(b.1(x0)))))
A.0(a.0(a.0(a.0(x0)))) → A.0(b.0(a.1(b.1(b.0(x0)))))
A.0(a.0(a.1(b.1(x0)))) → A.0(a.1(b.1(x0)))
A.0(a.0(a.1(b.1(b.1(b.1(b.1(y_0))))))) → B.1(b.1(b.1(b.1(b.1(y_0)))))
A.0(a.0(a.1(b.1(b.1(b.1(b.1(y_0))))))) → B.0(b.1(b.1(b.1(b.1(y_0)))))
A.0(a.0(a.1(b.1(b.1(b.1(y_0)))))) → B.1(b.1(b.1(b.1(b.1(y_0)))))
A.0(a.0(a.1(b.1(b.1(b.1(b.0(y_0))))))) → B.0(b.1(b.1(b.1(b.0(y_0)))))
A.0(a.0(a.0(a.0(x0)))) → A.1(b.0(a.1(b.1(b.0(x0)))))
A.0(a.0(a.1(b.0(x0)))) → A.0(a.1(b.0(x0)))
A.0(a.0(a.1(b.1(b.1(b.1(y_0)))))) → B.0(b.1(b.1(b.1(b.1(y_0)))))
A.0(a.0(a.1(b.1(b.1(b.0(y_0)))))) → B.0(b.1(b.1(b.1(b.0(y_0)))))
B.1(b.1(b.1(b.1(b.0(x0))))) → A.0(a.1(b.0(x0)))
The TRS R consists of the following rules:
b.1(b.1(b.0(x1))) → a.1(b.0(x1))
a.0(a.0(a.0(x1))) → a.1(b.1(b.0(x1)))
b.1(x0) → b.0(x0)
a.0(a.1(x1)) → a.1(b.0(a.1(x1)))
a.1(x0) → a.0(x0)
b.1(b.1(b.1(x1))) → a.1(b.1(x1))
a.0(a.0(a.1(x1))) → a.1(b.1(b.1(x1)))
a.0(a.0(x1)) → a.1(b.0(a.0(x1)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ ForwardInstantiation
↳ QDP
↳ ForwardInstantiation
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
A.0(a.0(a.1(b.1(b.0(x0))))) → A.0(b.0(a.1(b.0(x0))))
B.1(b.1(b.1(b.1(b.1(x0))))) → A.0(a.1(b.1(x0)))
A.0(a.0(a.1(b.1(b.1(b.1(b.0(y_0))))))) → B.1(b.1(b.1(b.1(b.0(y_0)))))
A.0(a.0(a.1(b.1(b.1(b.0(y_0)))))) → B.1(b.1(b.1(b.1(b.0(y_0)))))
A.0(a.0(a.0(x0))) → A.1(b.0(a.1(b.0(a.0(x0)))))
A.0(a.0(a.0(a.1(x0)))) → A.0(b.0(a.1(b.1(b.1(x0)))))
A.0(a.0(a.1(x0))) → A.0(b.0(a.1(b.0(a.1(x0)))))
A.0(a.0(a.1(b.1(b.1(x0))))) → A.1(b.0(a.1(b.1(x0))))
A.0(a.0(a.0(x0))) → A.0(b.0(a.1(b.0(a.0(x0)))))
A.0(a.0(a.1(b.1(b.0(x0))))) → A.1(b.0(a.1(b.0(x0))))
A.0(a.0(a.1(b.1(b.1(x0))))) → A.0(b.0(a.1(b.1(x0))))
A.0(a.0(a.1(x0))) → A.1(b.0(a.1(b.0(a.1(x0)))))
A.0(a.0(a.0(a.1(x0)))) → A.1(b.0(a.1(b.1(b.1(x0)))))
A.0(a.0(a.0(a.0(x0)))) → A.0(b.0(a.1(b.1(b.0(x0)))))
A.0(a.0(a.1(b.1(x0)))) → A.0(a.1(b.1(x0)))
A.0(a.0(a.1(b.1(b.1(b.1(b.1(y_0))))))) → B.1(b.1(b.1(b.1(b.1(y_0)))))
A.0(a.0(a.1(b.1(b.1(b.1(b.1(y_0))))))) → B.0(b.1(b.1(b.1(b.1(y_0)))))
A.0(a.0(a.1(b.1(b.1(b.1(y_0)))))) → B.1(b.1(b.1(b.1(b.1(y_0)))))
A.0(a.0(a.1(b.1(b.1(b.1(b.0(y_0))))))) → B.0(b.1(b.1(b.1(b.0(y_0)))))
A.0(a.0(a.0(a.0(x0)))) → A.1(b.0(a.1(b.1(b.0(x0)))))
A.0(a.0(a.1(b.0(x0)))) → A.0(a.1(b.0(x0)))
A.0(a.0(a.1(b.1(b.1(b.1(y_0)))))) → B.0(b.1(b.1(b.1(b.1(y_0)))))
A.0(a.0(a.1(b.1(b.1(b.0(y_0)))))) → B.0(b.1(b.1(b.1(b.0(y_0)))))
B.1(b.1(b.1(b.1(b.0(x0))))) → A.0(a.1(b.0(x0)))
The TRS R consists of the following rules:
b.1(b.1(b.0(x1))) → a.1(b.0(x1))
a.0(a.0(a.0(x1))) → a.1(b.1(b.0(x1)))
b.1(x0) → b.0(x0)
a.0(a.1(x1)) → a.1(b.0(a.1(x1)))
a.1(x0) → a.0(x0)
b.1(b.1(b.1(x1))) → a.1(b.1(x1))
a.0(a.0(a.1(x1))) → a.1(b.1(b.1(x1)))
a.0(a.0(x1)) → a.1(b.0(a.0(x1)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
The approximation of the Dependency Graph [15,17,22] contains 1 SCC with 16 less nodes.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ ForwardInstantiation
↳ QDP
↳ ForwardInstantiation
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
A.0(a.0(a.1(b.1(b.1(b.1(b.0(y_0))))))) → B.1(b.1(b.1(b.1(b.0(y_0)))))
B.1(b.1(b.1(b.1(b.1(x0))))) → A.0(a.1(b.1(x0)))
A.0(a.0(a.1(b.1(b.1(b.0(y_0)))))) → B.1(b.1(b.1(b.1(b.0(y_0)))))
A.0(a.0(a.1(b.1(x0)))) → A.0(a.1(b.1(x0)))
A.0(a.0(a.1(b.1(b.1(b.1(b.1(y_0))))))) → B.1(b.1(b.1(b.1(b.1(y_0)))))
A.0(a.0(a.1(b.1(b.1(b.1(y_0)))))) → B.1(b.1(b.1(b.1(b.1(y_0)))))
A.0(a.0(a.1(b.0(x0)))) → A.0(a.1(b.0(x0)))
B.1(b.1(b.1(b.1(b.0(x0))))) → A.0(a.1(b.0(x0)))
The TRS R consists of the following rules:
b.1(b.1(b.0(x1))) → a.1(b.0(x1))
a.0(a.0(a.0(x1))) → a.1(b.1(b.0(x1)))
b.1(x0) → b.0(x0)
a.0(a.1(x1)) → a.1(b.0(a.1(x1)))
a.1(x0) → a.0(x0)
b.1(b.1(b.1(x1))) → a.1(b.1(x1))
a.0(a.0(a.1(x1))) → a.1(b.1(b.1(x1)))
a.0(a.0(x1)) → a.1(b.0(a.0(x1)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By using the rule removal processor [15] with the following polynomial ordering [25], at least one Dependency Pair or term rewrite system rule of this QDP problem can be strictly oriented.
Strictly oriented dependency pairs:
A.0(a.0(a.1(b.1(b.1(b.1(b.0(y_0))))))) → B.1(b.1(b.1(b.1(b.0(y_0)))))
B.1(b.1(b.1(b.1(b.1(x0))))) → A.0(a.1(b.1(x0)))
A.0(a.0(a.1(b.1(x0)))) → A.0(a.1(b.1(x0)))
A.0(a.0(a.1(b.1(b.1(b.1(b.1(y_0))))))) → B.1(b.1(b.1(b.1(b.1(y_0)))))
A.0(a.0(a.1(b.0(x0)))) → A.0(a.1(b.0(x0)))
B.1(b.1(b.1(b.1(b.0(x0))))) → A.0(a.1(b.0(x0)))
Strictly oriented rules of the TRS R:
b.1(b.1(b.0(x1))) → a.1(b.0(x1))
a.0(a.0(a.0(x1))) → a.1(b.1(b.0(x1)))
b.1(x0) → b.0(x0)
b.1(b.1(b.1(x1))) → a.1(b.1(x1))
Used ordering: POLO with Polynomial interpretation [25]:
POL(A.0(x1)) = x1
POL(B.1(x1)) = 1 + x1
POL(a.0(x1)) = 1 + x1
POL(a.1(x1)) = 1 + x1
POL(b.0(x1)) = x1
POL(b.1(x1)) = 1 + x1
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ ForwardInstantiation
↳ QDP
↳ ForwardInstantiation
↳ QDP
↳ SemLabProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
A.0(a.0(a.1(b.1(b.1(b.0(y_0)))))) → B.1(b.1(b.1(b.1(b.0(y_0)))))
A.0(a.0(a.1(b.1(b.1(b.1(y_0)))))) → B.1(b.1(b.1(b.1(b.1(y_0)))))
The TRS R consists of the following rules:
a.0(a.1(x1)) → a.1(b.0(a.1(x1)))
a.1(x0) → a.0(x0)
a.0(a.0(a.1(x1))) → a.1(b.1(b.1(x1)))
a.0(a.0(x1)) → a.1(b.0(a.0(x1)))
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
The approximation of the Dependency Graph [15,17,22] contains 0 SCCs with 2 less nodes.
We have reversed the following QTRS:
The set of rules R is
b(b(b(x1))) → a(b(x1))
a(a(x1)) → a(b(a(x1)))
a(a(a(x1))) → a(b(b(x1)))
The set Q is empty.
We have obtained the following QTRS:
b(b(b(x))) → b(a(x))
a(a(x)) → a(b(a(x)))
a(a(a(x))) → b(b(a(x)))
The set Q is empty.
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
Q restricted rewrite system:
The TRS R consists of the following rules:
b(b(b(x))) → b(a(x))
a(a(x)) → a(b(a(x)))
a(a(a(x))) → b(b(a(x)))
Q is empty.
We have reversed the following QTRS:
The set of rules R is
b(b(b(x1))) → a(b(x1))
a(a(x1)) → a(b(a(x1)))
a(a(a(x1))) → a(b(b(x1)))
The set Q is empty.
We have obtained the following QTRS:
b(b(b(x))) → b(a(x))
a(a(x)) → a(b(a(x)))
a(a(a(x))) → b(b(a(x)))
The set Q is empty.
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS
Q restricted rewrite system:
The TRS R consists of the following rules:
b(b(b(x))) → b(a(x))
a(a(x)) → a(b(a(x)))
a(a(a(x))) → b(b(a(x)))
Q is empty.